Robust control of motion in presence of uncertain parameters and control constraints - Jastrzębski, Marcin; Kabziński, Jacek; Mosiołek, Przemysław (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The paper describes a novel, simple servo drive position controller, using solely the knowledge about the structure of the nonlinear model and the constraints met by individual components of the model. The desired behavior of the position and velocity signals is obtained by imposing a time-varying constraint on the signal aggregating information about the position and velocity tracking errors. The method allows you to determine the maximum control (servo drive current) necessary to achieve the control goal under the existing initial conditions and the selected reference trajectory. The control is constrained and consists in appropriate reaction when the trajectory approaches the barrier, the shape of which is responsible for the imposed properties of the transient and quasi-steady state tracking error. In addition to the derivation of the control, a discussion of its possible variants and basic properties is presented. Control with time-varying constraints has been introduced, which allows the control objectives to be met with limited conservatism of the imposed constraints. The influence of technical factors related to actual speed and position measurements was discussed and the operation of the real drive on a laboratory stand was presented.